STEREOTIP ISLAM DALAM SOUMISSION KARYA MICHEL HOULLEBECQ - Erwing, Erwing; Latjuba, Ade Yolanda; Hasbullah, Hasbullah (JURNAL ILMU BUDAYA, 2020)
The stereotype is a problem that we found when examining Michel Houllebecq's work entitled Soumission. As a form of prejudice against a particular ethnic / race or group, in this case, an Islamic group, this discourse is wrapped up in story elements. Therefore, to prove this thesis, this study is entitled "Islamic Stereotypes in Soumission by Michel Houllebecq". The aim is to describe the stereotypes of Islam that were built in the Soumission. The data collected was carried out using Albertine Minderop's characterization approach, namely: direct characterization (telling) and indirect characterization (showing), and also using the Luxembourg functional theory, connection events, and reference events by combining the concepts of Barthes sequences. The results showed that in the elements of the story, such as characters and characterizations as well as the flow of events showed Islamic stereotypes; that Islam is synonymous with terrorism, Islam legalizes polygamy, (women) Islam is fanatical about its religion, and Islam restricts women's rights.